# Unknown exponents causing problem to not be solved

Right now im trying to solve one of the problems i've encountered using sage and it seems like im onto something. However I've encountered a kink at step3 in my code.

x1, x2, l, p1, p2, a, b,  R= var('x1, x2, l, p1, p2, a, b,  R')
U = x1^a*x2^b
m = p1*x1+p2*x2;
L = m+ l * (R-U);
dLdx = L.diff(x1);
dLdy = L.diff(x2);
dLdl = L.diff(l);
step1=solve([dLdx == 0, dLdy == 0, dLdl == 0], p1, p2, R)
step2=solve(step1[0][0].rhs()/step1[0][1].rhs()==p1/p2,x1)
step3=solve(U.subs(step2)==R,x2)
step3

Out: x2^b == R/(a*p2*x2/(b*p1))^a


being that I want to isolate x2 im not sure why its power b is not just moved over.

why is this the case?

Note: The following code works

x1, x2, l, p1, p2, a, b,  Ubar= var('x1, x2, l, p1, p2, a, b,  Ubar')
assume(x1>0,x2>0,a>0,b>0)
U = x1*x2
m = p1*x1+p2*x2;
L = m+ l * (Ubar-U);
dLdx = L.diff(x1);
dLdy = L.diff(x2);
dLdl = L.diff(l);
step1=solve([dLdx == 0, dLdy == 0, dLdl == 0], p1, p2, Ubar)
step2=solve(step1[0][0].rhs()/step1[0][1].rhs()==p1/p2,x1)
step3good2=solve(U.subs(step2)==Ubar,x2)
step4good1=solve(step2[0].subs(step3Good2),x1)

step3good2

Out: [x2 == sqrt(R*p1/p2)]

step4good1

Out: [x1 == sqrt(R*p1/p2)*p2/p1]


This works because I'm considering a case where our utility function has no exponents a and b. What am I missing from my code?

edit retag close merge delete

Sort by ยป oldest newest most voted

In the output of your initial question, the unknown x2 has not been isolated, since it appears in both sides. You can formulate step2 in a more friendly way:

step2 = solve((p1/p2).subs(step1)==p1/p2, x1)


Likewise, borrowing an idea from this solution of another question, you can rewrite step3:

step3 = solve((U/R).subs(step2).log().log_expand()==0, x2)
step3


The output is

[x2 == e^(-a*log(a)/(a + b) + a*log(b)/(a + b) + a*log(p1)/(a + b) - a*log(p2)/(a + b) + log(R)/(a + b))]


Let see x2 in a more mathematical notation:

show(x2.subs(step3).canonicalize_radical())


This yields $$\frac{R^{\left(\frac{1}{a + b}\right)} b^{\frac{a}{a + b}} p_{1}^{\frac{a}{a + b}}}{a^{\frac{a}{a + b}} p_{2}^{\frac{a}{a + b}}}$$

more

This is great! Thank you!

( 2020-07-17 01:46:04 +0200 )edit

maybe you could accept @Juanjo 's answer, by checking the box just below <1>. I know it is not easy to understand that it is this button that validates the response, it took me a while before I understood it

( 2020-07-17 07:55:37 +0200 )edit

## Stats

Seen: 203 times

Last updated: Jul 17 '20